Infertilidad y su repercusión en la salud mental en una mujer adulta de 31 años de edad de la ciudad de Guayaquil del cantón Durán - Lema Yumailla, Adriana Estefani (2022)
The purpose of this investigation or case study is to determine the degree of affectation in the mental health of a 31-year-old adult woman in the city of Guayaquil in the Durán canton, for which techniques and tools necessary to obtain a diagnosis were applied. reliable and accurate in the face of the symptomatology manifested by the patient, the initial interview was used, allowing me to know the patient's personal data and her reason for consultation, on the other hand, clinical observation was necessary so that I could understand her body language, attaching the clinical history , where information was obtained from her childhood to the present and her family relationship, it should be noted that thanks to the psychometric tests and the reflected results, it was possible to define the existing pathology in the patient with infertility, such as depressive disorder with moderate episode, therefore which was according to his symptomatology and on his history of the psychopathological picture, the entire procedure was carried out Ocess through Cognitive Behavioral Therapy, in which rigid, negative thoughts were modified by flexible and positive ones, greater management of their impulses and emotions, denoting a passive behavior and according to the situation, for a better quality of life in the patient .